2013
DOI: 10.1117/1.jmm.12.4.041304
|View full text |Cite
|
Sign up to set email alerts
|

Plasma treatments to improve line-width roughness during gate patterning

Abstract: The major issue related to line width roughness (LWR) is the significant LWR of the photoresist patterns printed by 193-nm lithography that is partially transferred into the gate stack during the subsequent plasma etching steps. The strategy used today to overcome this issue is to apply postlithography treatments to reduce photoresist pattern LWR before transfer. In this article, we investigate the impact of various plasma treatments (HBr, H 2 , He, Ar) on the minimization of the LWR of dense and isolated phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
(32 reference statements)
1
7
0
Order By: Relevance
“…19 As the aforementioned derivations show, withinfeature variation, σ LWR ðLÞ, is affected by both the increase in correlation length and the increase in roughness exponent. For example, Azarnouche has shown that a combination of a VUV cure followed by etching steps increased the roughness exponent of a very long 80-nm wide feature from 0.57 to 0.9, and increased the correlation length of that feature from 16 to 41 nm.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…19 As the aforementioned derivations show, withinfeature variation, σ LWR ðLÞ, is affected by both the increase in correlation length and the increase in roughness exponent. For example, Azarnouche has shown that a combination of a VUV cure followed by etching steps increased the roughness exponent of a very long 80-nm wide feature from 0.57 to 0.9, and increased the correlation length of that feature from 16 to 41 nm.…”
Section: Discussionmentioning
confidence: 90%
“…A plot of the square-root of Eq (19). for the short-length linewidth roughness (LWR) at constant PSD(0) as a function of the line length L, in multiples of the correlation length ξ.…”
mentioning
confidence: 99%
“…Besides the LWR improvement, maintaining the integrity of the resist profile after plasma treatment is also a major challenge, which needs to be addressed . Plasma exposure induces profile and line width loss by resist shrinking, due to depletion and outgassing of organic material, or flowing mechanisms …”
Section: Resultsmentioning
confidence: 99%
“…It can be seen from Figure , that PR 8 has the highest roughness improvement. However, hydrogen plasma treatment is only able to reduce the mid and high frequency roughness …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation